Optimizing Human Resource Management in the Front Office Department: A Study on Employee Engagement and Service Quality - Laia, Serwita; Widagdo, C Susmono (MultiTech Publisher, 2025)
This research aims to explore how human resource management (HRM) strategies can be optimized to enhance employee engagement and service quality in the front office department of hotels. Using a qualitative research approach, this study collected data through semi-structured interviews with key managerial informants, including the Front Office Manager, Marketing Manager, and Human Resource Manager. The originality of this study lies in its managerial perspective, providing insights into the strategic implementation of HRM practices in hotel front office operations. The findings reveal that training and development, employee motivation and recognition, workload management, and interdepartmental coordination are critical to optimizing HRM in this department. However, challenges such as budget constraints, inconsistent reward systems, high job stress, and communication gaps hinder effectiveness. To address these issues, this study recommends the adoption of technology-driven training solutions, transparent performance-based incentives, AI-driven workforce scheduling, and digital communication platforms to improve service efficiency and employee satisfaction. The value of this research lies in its contribution to hospitality management literature by providing practical recommendations for enhancing HRM strategies in hotel front office operations. Future research should explore longitudinal impacts of HRM strategies, leadership influence on employee engagement, and employee perspectives to further improve workforce management in the hospitality industry